2011
DOI: 10.4061/2011/569416
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Induction of Inflammation by Pepsin in Acid in Bronchial Epithelial Cells

Abstract: Introduction. Gastroesophageal reflux has been associated with chronic inflammatory diseases and may be a cause of airway remodelling. Aspiration of gastric fluids may cause damage to airway epithelial cells, not only because acidity is toxic to bronchial epithelial cells, but also since it contains digestive enzymes, such as pepsin. Aim. To study whether pepsin enhances cytotoxicity and inflammation in airway epithelial cells, and whether this is pH-dependent. Methods. Human bronchial epithelial cells were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…For example, Johnston and colleagues (24) performed electron microscopy study and demonstrated that airway epithelial cells uptake pepsin by receptor-mediated endocytosis. Once internalized, pepsin is known to induce cytotoxicity, inflammatory response (e.g., up-regulation of IL-6 and IL-8), and airway remodeling (18). In addition, endotoxins are often found in gastric juice likely due to lysis of bacteria in the stomach (25).…”
Section: Gastroesophageal Reflux and Ipfmentioning
confidence: 99%
“…For example, Johnston and colleagues (24) performed electron microscopy study and demonstrated that airway epithelial cells uptake pepsin by receptor-mediated endocytosis. Once internalized, pepsin is known to induce cytotoxicity, inflammatory response (e.g., up-regulation of IL-6 and IL-8), and airway remodeling (18). In addition, endotoxins are often found in gastric juice likely due to lysis of bacteria in the stomach (25).…”
Section: Gastroesophageal Reflux and Ipfmentioning
confidence: 99%
“…Toward a more causal mechanism, an increasing number of investigators have independently developed their own pepsin assays and successfully identifi ed pepsin in the airways of a variety of lung pathologies: lung transplant patients, 28,29 interstitial lung disease, 30 pediatric patients, 10 and the critically ill. 6,11 Recognizing that pepsin itself is directly cytotoxic not just to the esophagus but also to the respiratory epithelium, 31 it may help to fi nally link the relationship between refl ux and lung pathology and explain why gastric acid-suppressive therapies have largely been ineffective in the treatment of presumed pulmonary manifestations of refl ux. 27,32 Unfortunately, controls in these airway pepsin studies have not consistently been reported, and, to our knowledge, only one study has tried to specifi cally examine for the presence of airway pepsin in a controlled setting using a qualitative pepsin assay in normal adults.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well reported clinical association between GER in SSc and lung involvement (18)(19)(20), data from animal models and in vitro analysis have provided a biologic rationale supporting the role of microaspiration in the genesis and/or progression of ILD. Pepsin and bile acids have a citotoxic effect on epithelial cells and can induce a pro-inflammatory response including expression of cytokines and chemokines (21)(22)(23). In a rat model of chronic aspiration, interstitial pneumonitis changes followed the instillation into the airways of either whole gastric or neutralized gastric fluid, but not of hydrochloric acid (24).…”
Section: The Role Of Pepsinmentioning
confidence: 99%